Integrating SIEM with Other Security Tools: Enhancing Cybersecurity Posture and Threat Response - Gupta Desetty, Avinash; Reddy Pulyala, Srinivas; Dutt Jangampet, Vinay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Security Information and Event Management (SIEM) systems have become essential to modern cybersecurity architectures. They enable organizations to collect, analyze, and correlate security data from multiple sources, offering a comprehensive view of their security posture. However, the effectiveness of SIEM is often limited by its isolation from other security tools. Integrating a Security Information and Event Management (SIEM) system with other security tools, such as firewalls, intrusion detection systems (IDS), and endpoint security solutions, can significantly improve an organization's cybersecurity posture and increase its ability to respond to threats. This integration allows for the seamless exchange of data and threat intelligence, breaking down silos and creating a unified security ecosystem that can detect, investigate, and respond to threats more effectively. This paper explores the benefits of integrating SIEM with other security tools, discusses the challenges of integrating different security architectures, and provides realworld examples of successful SIEM integrations.